2007
DOI: 10.1063/1.2738610
|View full text |Cite
|
Sign up to set email alerts
|

Particle image velocimetry study of turbulent flow over transverse square ribs in an asymmetric diffuser

Abstract: The objective of this paper is to study the combined effects of rib roughness and adverse pressure gradient produced in an asymmetric diffuser on turbulent flows. The two-dimensional asymmetric diffuser was comprised of a straight flat floor and a curved roof. The diffuser section was preceded and followed by straight parallel walls. The complete test conditions were comprised of a reference smooth floor and repeated arrays of transverse square ribs glued onto the floor to produce three pitch-to-height ratios,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…In this paper, the power law proposed by George and Castillo [24] is used to model the mean velocity profiles and to estimate U s . This particular power law and the log law have been used in the recent past to analyze smooth and rough-wall turbulent flows in zero pressure gradient boundary layers (Akinlade et al [35]; Kotey et al [36]), open channel flows (Bergstrom et al [37]) and flow over transverse ribs of varying pitch ratio in an asymmetric diverging channel (Tachie [21]). It was observed that the power law is capable of describing a wider extent of the mean velocity profiles than the log law.…”
Section: The Power Lawmentioning
confidence: 98%
See 1 more Smart Citation
“…In this paper, the power law proposed by George and Castillo [24] is used to model the mean velocity profiles and to estimate U s . This particular power law and the log law have been used in the recent past to analyze smooth and rough-wall turbulent flows in zero pressure gradient boundary layers (Akinlade et al [35]; Kotey et al [36]), open channel flows (Bergstrom et al [37]) and flow over transverse ribs of varying pitch ratio in an asymmetric diverging channel (Tachie [21]). It was observed that the power law is capable of describing a wider extent of the mean velocity profiles than the log law.…”
Section: The Power Lawmentioning
confidence: 98%
“…In fact, spatial averaging has been performed in a number of DNS and LES studies over transverse ribs. In this context, the PIV technique is well suited for studying rough-wall turbulent flows and such measurements (including spatially averaged statistics) have been reported over two-and three-dimensional ribs in open channel flows (Agelinchaab and Tachie [19]; Tachie et al [20]) and in asymmetric diverging channel (Tachie [21]). …”
Section: Introductionmentioning
confidence: 98%
“…The line averaged shear rates were also negative in value. All of these, along with the high H values observed in Figures 9 and 10, point to complications in flow characteristics similar to those observed in adverse pressure gradient flows [55]. This behavior is possibly due to the intermittent pores on the surface of the porous medium.…”
Section: Mean Velocities Momentum Flux and Vorticitymentioning
confidence: 53%
“…The value of H measured between columns 11 and 12 of the porous medium rods showed that the porous medium more than doubled the shape parameter of the boundary layer relative to the entry flow. This is predictable for obstructions in flow that generate higher drag characteristics such as that expected of the porous medium in the current flow arrangement [55].…”
Section: Mean Velocities Momentum Flux and Vorticitymentioning
confidence: 84%
“…The asymmetry observed in the profiles over the rough wall is in qualitative agreement with previous rough-wall boundary layer investigations. [43,44] The influence of Reynolds number and wall roughness on the upstream boundary layer is further examined using δ, θ , displacement thickness (δ * ) and shape factor (H = δ * /θ ). Wall roughness increased the boundary layer thicknesses, which is in qualitative agreement with previous studies over rough wall boundary layers.…”
Section: Upstream Boundary Layermentioning
confidence: 99%